Midsagittal tissue bridges are associated with walking ability in incomplete spinal cord injury: A magnetic resonance imaging case series. (3rd March 2020) - O'Dell, Denise R.; Weber, Kenneth A.; Berliner, Jeffrey C.; Elliott, James M.; Connor, Jordan R.; Cummins, David P.; Heller, Katherine A.; Hubert, Joshua S.; Kates, Megan J.; Mendoza, Katarina R.; Smith, Andrew C.
Abstract : Context : Following spinal cord injury (SCI), early prediction of future walking ability is difficult, due to factors such as spinal shock, sedation, impending surgery, and secondary long bone fracture. Accurate, objective biomarkers used in the acute stage of SCI would inform individualized patient management and enhance both patient/family expectations and treatment outcomes. Using magnetic resonance imaging (MRI) and specifically a midsagittal T2-weighted image, the amount of tissue bridging (measured as spared spinal cord tissue) shows potential to serve as such a biomarker. Ten participants with incomplete SCI received MRI of the spinal cord. Using the midsagittal T2-weighted image, anterior and posterior tissue bridges were calculated as the distance from cerebrospinal fluid to the damage. Then, the midsagittal tissue bridge ratio was calculated as the sum of anterior and posterior tissue bridges divided by the spinal cord diameter. Each participant also performed a 6-minute walk test, where the total distance walked was measured within six minutes. Findings : The midsagittal tissue bridge ratio measure demonstrated a high level of inter-rater reliability (ICC = 0.90). Midsagittal tissue bridge ratios were significantly related to distance walked in six minutes ( R  = 0.68, P = 0.03). Conclusion/clinical relevance : We uniquely demonstrated that midsagittal tissue bridge ratios were correlated walking ability. These preliminary findings suggest potential for this measure to be considered a prognostic biomarker of residual walking ability following SCI.